2012
DOI: 10.1371/journal.pone.0032179
|View full text |Cite
|
Sign up to set email alerts
|

Complete Mitochondrial DNA Analysis of Eastern Eurasian Haplogroups Rarely Found in Populations of Northern Asia and Eastern Europe

Abstract: With the aim of uncovering all of the most basal variation in the northern Asian mitochondrial DNA (mtDNA) haplogroups, we have analyzed mtDNA control region and coding region sequence variation in 98 Altaian Kazakhs from southern Siberia and 149 Barghuts from Inner Mongolia, China. Both populations exhibit the prevalence of eastern Eurasian lineages accounting for 91.9% in Barghuts and 60.2% in Altaian Kazakhs. The strong affinity of Altaian Kazakhs and populations of northern and central Asia has been reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 88 publications
(201 reference statements)
5
59
0
Order By: Relevance
“…Native Siberians, including populations from Sakha, continually receive attention in relation to the colonization of the Americas [15-18], whereas phylogenetic analyses of their uniparental data have added valuable information about the colonization and re-colonization of northeastern Eurasia. The analysis of Siberian mtDNA pool has provided evidence to rule out the existence of a northern Asian route for the initial human colonization of Asia [19], and revealed that the present-day northern Asian maternal gene pool consists of predominantly post-LGM components of eastern Asian ancestry [20,21]. The most frequent Y-chromosome haplogroup in northern Eurasia – N1c – most probably arose in present day China and spread to Siberia after the founder event associated with the human entry into the Americas [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Native Siberians, including populations from Sakha, continually receive attention in relation to the colonization of the Americas [15-18], whereas phylogenetic analyses of their uniparental data have added valuable information about the colonization and re-colonization of northeastern Eurasia. The analysis of Siberian mtDNA pool has provided evidence to rule out the existence of a northern Asian route for the initial human colonization of Asia [19], and revealed that the present-day northern Asian maternal gene pool consists of predominantly post-LGM components of eastern Asian ancestry [20,21]. The most frequent Y-chromosome haplogroup in northern Eurasia – N1c – most probably arose in present day China and spread to Siberia after the founder event associated with the human entry into the Americas [22].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing mtDNA data from Sakha populations were obtained by the examination of hypervariable segment I (HVSI) sequences and a limited number of coding region markers, thus permitting to determine the main haplogroups only. However, analyses of large data sets of eastern [31,32] and northern Asian complete mtDNA sequences [19-21,30,33,34] have significantly refined the topology of the mtDNA phylogeny, providing new informative markers for large scale population studies. This was an essential prerequisite to clarify the events that led to the re-colonization of Siberia, as most of the newly defined sub-haplogroups common in Siberia have been dated as post-LGM [20,21,35].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of these components in the mtDNA pool of Slavs was probably of two origins: some of them point to relatively recent (medieval) contacts between Slavic and non-Slavic populations [30], [32], but some of them testify to earlier contacts (as early as 10 kya) occurred in European prehistory [33][35]. Thus, in order to deepen the understanding of complex Slavic history and unravel their interactions with other ethnic groups, we demonstrate here the results of complete mitochondrial genome characterization of several non-European lineages (East Eurasian A, C, D, G and African L haplogroups) found in populations of Poles and Ukrainians.…”
Section: Introductionmentioning
confidence: 99%
“…We did, however, observe stark differences between the Iron Age Siberians and modern Siberians that contain higher frequencies of common Eastern Eurasian haplogroups, such as M (Derenko et al, 2012;Gonzalez Ruiz et al, 2012). Our results would therefore suggest the Pazyryk and Tagar peoples either had greater contact with West Eurasian peoples, or their ancestors originated or had close connections with the hunter-gatherers of Paleolithic Europe.…”
Section: Discussionmentioning
confidence: 49%